The prevalence and associated factors of success of labor induction in Hargeisa maternity hospitals, Hargeisa Somaliland 2022: a hospital-based cross-sectional study - Fatima Qasim Farah; Getie Lake Aynalem; Asmra Tesfahun Seyoum; Getachew Muluye Gedef (BMC, 2023)
Abstract Background The induction of labor is an artificial initiation of labor and has become one of the most common interventions in modern obstetrics to improve maternal and neonatal health. Understanding the prevalence and pregnancy outcomes following labor inductions is crucial in regions with high rates of maternal mortality and morbidity because of insufficient access to comprehensive emergency obstetric care. Therefore, this study aimed to assess the prevalence and associated factors of the success of induction of labor in Hargeisa maternity hospital Somaliland. Methods A hospital-based cross-sectional study was employed among 453 women in Hargeisa maternity hospitals, Somaliland from January 1st to March 30th, 2022. Data were entered using Epi data version 4.6 and analyzed by using SPSS version 25. Bivariable and multivariable logistic regression were used to identify the associated factors with the success of labor induction and an odds ratio with a 95% confidence interval was used to measure the strength of the association. A P-value of ≤ 0.05 was considered statistically significant in multivariate analysis. Results Of a total of 453 study participants who had undergone induction of labor, 349 (77%) of them had successful induction of labor with a 95% CI: 73%, 81%. Favorable Bishop score (AOR = 3.45, 95% CI: 1.98, 5.99), time from the start of induction to delivery < 12 h (AOR = 4.01, 95% CI: 2.16, 7.450), non-reassuring fetal heart rate pattern (AOR = 0.42, 95% CI: 0.22, 0.78) and amniotic fluid change to meconium (AOR = 0.43, 95% CI: 0.23, 0.79) were significantly associated with the success of labor induction. Conclusion This study implies that three out of four women who underwent induction had successful induction of labor. Favorable bishop score, time from the start of induction to delivery < 12 h, non-reassuring fetal heart rate pattern, and amniotic fluid change to meconium were significantly associated with the success of labor induction. The hospital should establish a clear bishop scoring system and there should be a strict follow-up on the condition of the fetal heartbeat and take corrective actions as needed. The factors related to healthcare facilities and providers need to be addressed by additional prospective studies.